(untitled) (Conferencea, 2024)
Proverbs do not lose their relevance, despite the changes that have recently been made by technology and the transfer of communication to the digital space. Interest in proverbs appears in newspapers, public speaking, everyday communication, and in the scientific community. This article is devoted to the consideration of proverbs, their functions, role, and comparative analysis of representation temporal relations of English and Uzbek proverbs.